2016
DOI: 10.1021/acs.jmedchem.5b01293
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Metabolite Identification Coupled with Automated Ligand Identification System (ALIS) Technology: A Novel Approach to Uncover Structure–Activity Relationships and Guide Drug Design in a Factor IXa Inhibitor Program

Abstract: A potent and selective Factor IXa (FIXa) inhibitor was subjected to a series of liver microsomal incubations, which generated a number of metabolites. Using automated ligand identification system-affinity selection (ALIS-AS) methodology, metabolites in the incubation mixture were prioritized by their binding affinities to the FIXa protein. Microgram quantities of the metabolites of interest were then isolated through microisolation analytical capabilities, and structurally characterized using MicroCryoProbe he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
2
10
0
2
Order By: Relevance
“…ALIS is currently the most prevailing MS-based technique employed in pharmaceutical companies for HTS of large-scale synthetic compound libraries. 256,261,[270][271][272][273] This system integrates size exclusion chromatography for isolating protein-ligand complexes and reverse-phase chromatography for dissociating bound ligands, which are then identified by high-resolution MS. Not surprisingly, the application of ALIS to ligand screening for GPCRs substantially lagged behind soluble proteins due to difficulties in obtaining membrane receptors of sufficient purity and stability. The earliest application was ligand screening for M2R, 274 in which purified M2R was incubated with a 1500-compound pool in each round of affinity selection.…”
Section: Novel Screening Technologymentioning
confidence: 99%
“…ALIS is currently the most prevailing MS-based technique employed in pharmaceutical companies for HTS of large-scale synthetic compound libraries. 256,261,[270][271][272][273] This system integrates size exclusion chromatography for isolating protein-ligand complexes and reverse-phase chromatography for dissociating bound ligands, which are then identified by high-resolution MS. Not surprisingly, the application of ALIS to ligand screening for GPCRs substantially lagged behind soluble proteins due to difficulties in obtaining membrane receptors of sufficient purity and stability. The earliest application was ligand screening for M2R, 274 in which purified M2R was incubated with a 1500-compound pool in each round of affinity selection.…”
Section: Novel Screening Technologymentioning
confidence: 99%
“…The ALIS system can be used to rank order the binding affinity of metabolites to enzymes. For the first time, Zhang et al (2016) have demonstrated that ALIS can reveal highly potent metabolites of Factor IXa without the need of isolating each metabolite. Chemical structures of metabolites were elucidated.…”
Section: Indirect Ba‐ms Methods Relying On Size Exclusion Chromatographymentioning
confidence: 99%
“…As a Type I 1/2 kinase inhibitor, SCH772984 is a promising inhibitor targeting ERK1/2 with high bioactivity, and we have previously studied the interaction mechanisms of SCH772984 with ERK2. 14 Aerwards, Deng and coworkers discovered compound 1 as an effective selective ERK2 inhibitor through the automated ligand identication system (ALIS), 15 and meanwhile they obtained the crystal structure of human ERK2 bound compound 1 (PDB ID: 4QYY 16 ). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%